Fetal outcome in antepartum haemorrhage: a study at a tertiary care centre - Radhika M Gadgi; Annie Rajaratnam (Barpeta Obstetrics and Gynaecological Society, 2023)
Objectives: The objectives of the present research are to study the fetal outcome in antepartum haemorrhage (APH) and the associated risk factors contributing to fetal morbidity and mortality. Materials & methods: The present observational study includes total 77 cases diagnosed with APH during the study period (June 2017 to March 2020). The parameter of the patients that were documented in the study includes demographic data of the new born, cause for APH, fetal outcome. Result: The institutional prevalence of antepartum hemorrhage (APH) was 1.78%. The main causes of APH in patients were abruption (51.97%) and placenta previa (44.15%). The mean birth weight was significantly high in fetus with placenta previa complication (2.56±0.42 Kg) in comparison to abruption (2.19±0.78 Kg). The mean APGAR scores (1 min and 5 min) were significantly high in fetus with placenta previa complication in comparison to abruption. The perinatal mortality in placenta previa and abruption was 5.40% and 15% respectively. Conclusion: APH is an obstetrical high-risk entity and one of the most important cause of perinatal mortality and morbidity. Therefore, prevention, early detection, management and appropriate clinical treatment is vital.